Graphene-based saturable absorber for single-longitudinal-mode operation of highly doped erbium-doped fiber laser - Muhammad, Farah Diana; Zulkifli, Mohd Zamani; Abdul Latif, Amirah; Harun, Sulaiman Wadi; Ahmad, H. (IEEE, 2012)
In this paper, a conventional wavelength band (C-band) fiber laser with a tunable single-longitudinal-mode (SLM) output using multilayer graphene as a saturable absorber is demonstrated. The proposed fiber laser uses a short length of highly doped erbium-doped fiber (EDF) as the gain medium and a fiber ferrule with graphene flakes adhered to it by index matching gel (IMG) that acts as the saturable absorber. The fiber laser is able to generate an adjustable wavelength output between 1547.88 and 1559.88 nm with an average peak power of 6.48 dBm with a measured signal-to-noise ratio between 66.0 and 68.3 dB. The SLM output is verified by the absence of frequency beating in the radio frequency (RF) spectrum output and by a measured linewidth of 206.25 kHz using the self-heterodyne technique. The deposition of graphene flakes on the fiber ferrule using the IMG is a new and effective technique to generate SLM operation in the fiber laser